The Urgency of Uzlah from the Perspective of Abu Hamid Al-Ghazali - Fadhila Sidiq Permana (Tasamuh: Jurnal Studi Islam, 2026)
The theme of uzlah is still very important to study in addressing various social problems that exist in everyday life. Many life issues arise due to human negligence in getting closer to their God, as most of their time is consumed by various worldly interests or activities. This article aims to revive the classical Sufi teachings about the urgency of uzlah. The method used in this research is a literature study that places the book Ihya' Ulumiddin by al-Ghazali as its research object. The urgency of uzlah according to al-Ghazali is to avoid various sins, reduce excessive hope in creatures, and break the traits of greed. The urgency of uzlah proposed by al-Ghazali is still very relevant to be applied and developed in the contemporary era like now.